2021
DOI: 10.1111/gcb.15494
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of oyster reefs by mangroves: Unexpected climate‐driven ecosystem shifts

Abstract: Increases in minimum air temperatures have facilitated transitions of salt marshes to mangroves along coastlines in the southeastern United States. Numerous studies have documented mangrove expansion into salt marshes; however, a present‐day conversion of oyster reefs to mangrove islands has not been documented. Using aerial photographs and high‐resolution satellite imagery, we determined percent cover and number of mangrove patches on oyster reefs in Mosquito Lagoon, FL, USA over 74 years (1943–2017) by digit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 68 publications
(113 reference statements)
0
17
0
Order By: Relevance
“…For example, reef-building oysters require hard substrates for settlement, and tropical oysters can be found attached to rocks, mangrove roots and coral reefs, and many species rely on these habitats to form biogenic reef structures (Table 1). Driven by climate change, oyster reefs in parts of the subtropical southeast USA are being replaced by mangroves, primarily Rhizophora mangle, from tropical areas (Mcclenachan et al, 2021). Both the tropical Crassostrea rhizophorae and eurythermal Crassostrea virginica have been documented growing on the roots of R. mangle (C. rhizophorae exclusively so) (Aquino-Thomas and Proffitt, 2014; Lodeiros et al, 2020), however the preferred habitat of C. virginica is hard rocky substrates (Carranza et al, 2009).…”
Section: Habitat Associationsmentioning
confidence: 99%
“…For example, reef-building oysters require hard substrates for settlement, and tropical oysters can be found attached to rocks, mangrove roots and coral reefs, and many species rely on these habitats to form biogenic reef structures (Table 1). Driven by climate change, oyster reefs in parts of the subtropical southeast USA are being replaced by mangroves, primarily Rhizophora mangle, from tropical areas (Mcclenachan et al, 2021). Both the tropical Crassostrea rhizophorae and eurythermal Crassostrea virginica have been documented growing on the roots of R. mangle (C. rhizophorae exclusively so) (Aquino-Thomas and Proffitt, 2014; Lodeiros et al, 2020), however the preferred habitat of C. virginica is hard rocky substrates (Carranza et al, 2009).…”
Section: Habitat Associationsmentioning
confidence: 99%
“…Areal coverage of natural intertidal C. virginica reefs within ML declined 24% between 1943 and 2009 [3], primarily in popular boating areas due to boat wakes dislodging live oyster clusters and depositing shells above the intertidal zone where survival plus natural recolonization are not possible [4]. Oyster reefs situated in shallow bays and tidal creeks bordered by mangroves and salt marsh plants did not change in aerial coverage over this same time frame [37]. This loss of oyster reef habitat, coupled with declining water quality in ML, initiated a community-based restoration effort in 2007 that remains on-going.…”
Section: Site Description and Experimental Approachmentioning
confidence: 99%
“…This study, as well as previous studies in ML, have all demonstrated a strong "reef effect" for sediment biogeochemical parameters, meaning each individual reef tends to be highly unique, including those within the same treatment or category [20,40]. Causes for this high within-treatment variability include the unique site histories of each reef, differences in local flow patterns, proximity to nutrient or pollution sources, exposure to boat traffic or other stressors, spatial variation in disease or predation, and mangrove encroachment [4,37]. Therefore, the low number of replicate reefs, the high within-treatment variability, and the naturally heterogeneous nature of many of the sediment biogeochemical parameters measured, all contributed to low statistical power for the field BACI experiment.…”
Section: Performance Of Bese Under Field Conditionsmentioning
confidence: 99%
“…Similarly, mangroves can reduce sedimentation and salinity stress for other mangroves or other foundation species such as oysters (Aquino- Thomas and Proffitt, 2014). Oyster reefs can, in turn, provide new habitat for mangroves to colonize, and augment the settlement of mangrove propagules (McClenachan et al, 2021). As such, by fostering beneficial interactions between neighboring conspecifics, the dense restoration of these intertidal keystone species can provide improved restoration success.…”
Section: Mangrove Habitat Requirementsmentioning
confidence: 99%